(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The scientific article analyzes the causes of dental caries, one of the diseases of the oral cavity in humans, the mechanism of its development, and modern methods of its treatment. The article provides information on preventive measures, improving hygiene culture, as well as treatment methods implemented using new technologies. The advantages of innovative approaches in dentistry, such as laser therapy, remineralization, and filling with composite materials, are shown to patients. The study emphasizes the importance of early detection of caries in the cases of patients who come to the Dental Clinic with an appeal, and provides recommendations aimed at maintaining a healthy tooth structure.